Corrosion inhibition of Fe-19Cr stainless steel by glutamic acid in 1M HCl - Hamadi, Latifa; Kareche, Abdelhak; Mansouri, Salah; Benbouta, Soumia (Chemical Data Collections, 2020)
Electrochemical methods, weight loss and surface analysis technique were used to study the effect of glutamic acid on the corrosion of Fe-19Cr stainless steel in 1 M hydrochloric acid solution. Results revealed that the corrosion inhibition of glutamic acid of Fe-19Cr in 1 M HCl was enhanced in the presence of the iodide ions due to synergistic effect. In the absence of KI, the inhibition of Fe-19Cr corrosion by glutamic acid was glutamic acid concentration dependent. Potentiodynamic polarization curves demonstrated that glutamic acid acts as a mixed type inhibitor. Self-Assembled Monolayers of glutamic acid were able to protect stainless steel from corrosion effectively. The adsorption of the inhibitor onto the stainless steel surface follows Langmuir adsorption isotherm. The value of free energy of the adsorption indicated that there is a physical interaction between the glutamic acid and the stainless steel surface.